O doce saber da terra: tecendo saberes no Semiárido/Sertão - Figueiredo, Gustavo de Alencar (2021)
This research is delineated as a human development action in the historical trajectory of a singular element located in the rural community of Vila Riacho do Meio, located in the municipality of Cajazeiras - PB: The Riacho do Meio Mill. A research perspective was adopted that allowed us to transcend the limits of fragmented school knowledge and, at the same time, create a polyphony that made it possible to insert in school other ways of reading, understanding and interpreting the world. The focus of the study from which this doctoral dissertation was generated was the sociocultural practices underlying the work carried out at Engenho do Riacho do Meio, which are assumed to be educational practices, based on traditional knowledge without leaving the knowledge of science apart. Based on the principles of complexity (Edgar Morin) and the characterization of traditional knowledge (Conceição Almeida and Chico Lucas), the notion of method was adopted as an open and emerging strategy and, based on it, it was possible to build a human and humanizing narrative of the Riacho do Meio Mill, understood and experienced as the universe of research developed and reported in this study. Its essential purpose was to weave a complex and transdisciplinary web, linking traditional knowledge implicit in the manufacturing practices of sugarcane-derived products and the scientific knowledge associated with these practices. The autobiographical testimonial narrative was used as a discursive strategy, which allowed rescuing the life experiences of both the researcher and the workers at Engenho, revealing how they organize their historically shared knowledge through tradition. It is intended to continue this work through the reconversion of The Riacho do Meio Mill as a living space in the Semiarid/Sertao that enables the university-community articulation, providing adequate conditions for the construction of an authentic dialogue between scientific knowledge studied in school spaces and the ancestral knowledge historically produced by men and women who give life to the human existence characteristic of The Riacho do Meio Mill.